2011
DOI: 10.1007/s00262-011-1134-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased lymphocyte infiltration in patients with head and neck cancer treated with the IRX-2 immunotherapy regimen

Abstract: Twenty-seven subjects with squamous cell cancer of the head and neck received the neoadjuvant IRX-2 immunotherapy regimen prior to surgery in a Phase 2 trial. Pretreatment tumor biopsies were compared with the primary tumor surgical specimens for lymphocyte infiltration, necrosis and fibrosis, using hematoxylin and eosin stain and immunohistochemistry in 25 subjects. Sections were examined by three pathologists. Relative to pretreatment biopsies, increases in lymphocyte infiltration (LI) were seen using H and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…Tumor infiltration by cytotoxic CD3 + CD8 + CTLs has been attributed a positive prognostic value in cohorts of breast carcinoma patients (n = 1334), positively correlating with tumor grade and inversely correlating with age at diagnosis, estrogen receptor as well as progesterone receptor positivity; 44 differentiated thyroid carcinoma patients (n = 398); 45 subjects affected by oral squamous cell carcinoma (n = 132); 46 glioblastoma patients vaccinated with DC-based immunotherapy (n = 23); 47 subjects affected by esophageal carcinoma (n = 70); 48 non-small cell lung carcinoma (NSCLC) patients (n = 199), highlighting a preponderant prognostic value for T cells infiltrating cancer nests and the tumor stroma; 49 subjects affected by melanoma (n = 264 and n = 285), a setting in which T-cell infiltration appears to convey independent prognostic information; 50 , 51 surgically resected HCC patients (n = 44); 52 Merkel cell carcinoma patients (n = 146); 53 subjects affected by colorectal carcinoma (CRC) (n = 447, n = 276, n = 41, n = 93, n = 152, n = 97; n = 160 and n = 470); 54 - 61 ovarian carcinoma patients who underwent surgical resection (n = 70); 62 prostatic adenocarcinoma patients (n = 325); 63 and subjects affected by muscle-invasive urothelial carcinoma (n = 69) 64 . Similarly, increased intratumoral levels of both CD3 + CD8 + CTLs and not better characterized CD3 + CD4 + helper T cells have been associated with improved clinicopathological parameters in cohorts of head and neck carcinoma (HNC) patients treated with IRX-2-based immunotherapy (n = 15, n = 42 and n = 27); 65 - 67 esophageal cancer patients who underwent tumor resection (n = 122 and n = 181), a setting in which NK-cell accumulation also conveyed prognostic information; 68 , 69 surgically resected NSCLC patients (n = 335), highlighting a prominent prognostic value for CD4 + cells accumulating at stromal, as opposed to epithelial, sites; 70 subjects affected by melanoma; 71 surgically resected HCC patients (n = 163); 72 pancreatic adenocarcinoma patients (n = 80), correlating with an intense infiltration by DCs; 73 gallbladder cancer patients treated with curative surgery (n = 110), a setting in which also DC, but not NK-cell, infiltration, conveyed prognostic information; 74 prostate carcinoma patients undergoing radical prostatectomy (n = 188), a setting in which B-cell infiltration also provided prognostic insights; 75 vulval intraepithelial neoplasia patients receiving therapeutic human papillomavirus vaccination combined with the Toll-like receptor (TLR) 7 agonist imiquimod (n = 19), 76 and patients affected by various solid tumors (including breast carcinoma, melanoma and renal cell carcinoma, RCC) undergoing IL-2-based immunotherapy 77 . Of note, CD3 + CD4 + and CD8 + cells (together with CD20 + and CD57 + cells) have been shown to preferentially accumulate at the margins of breast carcinoma lesions ablated by high intensity focused ultrasound (n = 23 patients), as opposed to similar lesions removed by radical mastectomy (n = 25) …”
Section: T Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor infiltration by cytotoxic CD3 + CD8 + CTLs has been attributed a positive prognostic value in cohorts of breast carcinoma patients (n = 1334), positively correlating with tumor grade and inversely correlating with age at diagnosis, estrogen receptor as well as progesterone receptor positivity; 44 differentiated thyroid carcinoma patients (n = 398); 45 subjects affected by oral squamous cell carcinoma (n = 132); 46 glioblastoma patients vaccinated with DC-based immunotherapy (n = 23); 47 subjects affected by esophageal carcinoma (n = 70); 48 non-small cell lung carcinoma (NSCLC) patients (n = 199), highlighting a preponderant prognostic value for T cells infiltrating cancer nests and the tumor stroma; 49 subjects affected by melanoma (n = 264 and n = 285), a setting in which T-cell infiltration appears to convey independent prognostic information; 50 , 51 surgically resected HCC patients (n = 44); 52 Merkel cell carcinoma patients (n = 146); 53 subjects affected by colorectal carcinoma (CRC) (n = 447, n = 276, n = 41, n = 93, n = 152, n = 97; n = 160 and n = 470); 54 - 61 ovarian carcinoma patients who underwent surgical resection (n = 70); 62 prostatic adenocarcinoma patients (n = 325); 63 and subjects affected by muscle-invasive urothelial carcinoma (n = 69) 64 . Similarly, increased intratumoral levels of both CD3 + CD8 + CTLs and not better characterized CD3 + CD4 + helper T cells have been associated with improved clinicopathological parameters in cohorts of head and neck carcinoma (HNC) patients treated with IRX-2-based immunotherapy (n = 15, n = 42 and n = 27); 65 - 67 esophageal cancer patients who underwent tumor resection (n = 122 and n = 181), a setting in which NK-cell accumulation also conveyed prognostic information; 68 , 69 surgically resected NSCLC patients (n = 335), highlighting a prominent prognostic value for CD4 + cells accumulating at stromal, as opposed to epithelial, sites; 70 subjects affected by melanoma; 71 surgically resected HCC patients (n = 163); 72 pancreatic adenocarcinoma patients (n = 80), correlating with an intense infiltration by DCs; 73 gallbladder cancer patients treated with curative surgery (n = 110), a setting in which also DC, but not NK-cell, infiltration, conveyed prognostic information; 74 prostate carcinoma patients undergoing radical prostatectomy (n = 188), a setting in which B-cell infiltration also provided prognostic insights; 75 vulval intraepithelial neoplasia patients receiving therapeutic human papillomavirus vaccination combined with the Toll-like receptor (TLR) 7 agonist imiquimod (n = 19), 76 and patients affected by various solid tumors (including breast carcinoma, melanoma and renal cell carcinoma, RCC) undergoing IL-2-based immunotherapy 77 . Of note, CD3 + CD4 + and CD8 + cells (together with CD20 + and CD57 + cells) have been shown to preferentially accumulate at the margins of breast carcinoma lesions ablated by high intensity focused ultrasound (n = 23 patients), as opposed to similar lesions removed by radical mastectomy (n = 25) …”
Section: T Lymphocytesmentioning
confidence: 99%
“…Tumor infiltration by CD68 + macrophages has been linked to worsened disease course in cohorts of breast carcinoma patients (n = 249), in relationship with increased microvessel density and VEGF expression; 239 HNC patients who underwent surgery for the removal of laryngeal lesions (n = 98); 240 patients subjected to potentially curative resection of esophageal cancers (n = 56 and n = 121); 241 , 242 resected gastric cancer patients (n = 97), 243 subjects with resected HCC (n = 137); 244 lung adenocarcinoma patients (n = 113), again in association with increased local angiogenesis; 245 pleural mesothelioma patients who underwent cytoreductive surgery (n = 52), a setting in which also circulating monocytes correlated with poor survival; 246 melanoma patients (n = 58, n = 202 and n = 190), high macrophage counts being associated with markers of aggressive disease including Breslow thickness, ulceration and mitotic rate; 87 , 247 , 248 subjects affected by ovarian carcinoma (n = 67); 249 bladder cancer patients receiving intravesical instillations of the bacillus Calmette-Guérin (BCG) (n = 41); 250 prostate cancer patients treated with hormonal therapy (n = 71), a setting in which macrophage infiltration was shown to predict resistance to treatment; 251 and patients affected by renal pelvis and ureteral transitional cell carcinomas (n = 75) 252 . Conversely, tumor infiltration by macrophages (most often detected as CD68 + cells) has been correlated with improved disease outcome in cohorts of HNC patients bearing nasopharyngeal lesions (n = 45) 212 or treated with IRX-2-based immunotherapy (n = 27); 67 patients bearing differentiated thyroid carcinoma (n = 398); 45 NSCLC patients who underwent surgical resection (n = 175) 253 or receiving chemotherapy for stage IV lesions (n = 199); 49 gastric cancer patients (n = 84), highlighting a correlation between intratumoral macrophages, intratumoral CD8 + T cells and tumor cell apoptosis; 254 HCC patients who underwent surgical resection (n = 302); 96 melanoma patients treated with oral BCG (n = 25); 255 CRC patients (n = 97, n = 70, n = 446 and n = 160), overall suggesting a critical role of macrophages at the tumor invasive margin; 60 , 256 - 258 and patients affected by various solid tumors (including breast carcinoma, melanoma and RCC) subjected to IL-2-based immunotherapy 77 . Along similar lines, intense tumor infiltration by CD14 + CD40 + macrophages has been shown to constitute an independent prognostic factor in a cohort of CRC patients (n = 31) 259 …”
Section: Macrophagesmentioning
confidence: 99%
“…Rarely have these pharmacologic strategies been applied to eliminating immune suppression mediated by Treg in cancer. A good example of this approach is a phase II trial of IRX-2, a biologic containing several cytokines, administered to patients with advanced HNSCC in the adjuvant setting in conjunction with daily doses of indomethacin in order to silence suppressor cells [76]. Traditionally, Treg depletion has been used to improve endogenous anti-tumor immunity and the efficacy of immunotherapies usin strategies such as the administration of low-dose cyclophosphamide, daclizumab (anti-CD25 Ab), denileukin diftitox (Ontak) or tyrosine kinase inhibitors (TKIs) such as Sunitinb [7779].…”
Section: Pharmacologic Interventions Targeting the Adenosinergic Pmentioning
confidence: 99%
“…Translational studies revealed several possible mechanisms explaining the observed IRX-2-associated antitumor responses. Thus, it has been shown that IRX-2 increases the number of circulating native and memory T cells and enhances lymphocytic infiltration into tumor-draining lymph nodes [35]. In addition, in vitro studies showed that IRX-2 matures human monocyte-derived dendritic cells (DC) and protects T cells from tumor-induced apoptosis [6, 7].…”
Section: Introductionmentioning
confidence: 99%